Bony tongue: a rare base of tongue Osseus Choristoma case report - Ab Rahman, Redha Asyrafi; Md Soleh, Mohd Najeb; Ramli, Ramiza Ramza; Bakrin, Ikmal Hisyam (Elsevier, 2022)
Osseus Choristoma is a normal bone tissue that develops ectopically in a region otherwise devoid of bone formation. It is usually developed at the dorsum of the posterior third tongue in the oral region, specifically at the circumvallate papilla region near the foramen caecum. Definitive diagnosis is by histopathological examination, and surgical excision is the treatment of choice. The etiology, however, remains debatable. In this paper, we reported this rare case report of a base of tongue osseous choristoma, which is located posterior to the terminal sulcus of the tongue.